Finite element modelling of short steel tubes filled with rubberized concrete. (15th August 2016) - Duarte, A.P.C.; Silva, B.A.; Silvestre, N.; de Brito, J.; Júlio, E.; Castro, J.M.
Abstract: This paper presents a numerical investigation on the ductility and strength of short steel tubes filled with Rubberized Concrete (RuC), which is a composite material that mixes concrete with rubber particles. This research concerns the enhancement of both ductility and energy absorption of CFST by considering a core of RuC instead of normal concrete (NC). First, a brief literature review on the topic is presented. Then, based on an experimental programme conducted by the authors, numerical models of CFST and RuCFST columns are developed. The results of non-linear analyses (ultimate strengths, load-shortening curves and failure modes) are validated using experimental data, and good agreement is shown. Finally, a numerical study on the properties of confined NC and RuC is conducted. It is concluded that the concrete damaged plasticity model can be used to simulate RuC. The dilation angle plays a key role in RuC and its lower value (compared to that of NC) influences the concrete confinement. Taking into account the RuC dilation angle, steel yield stress and tube local slenderness, a new formula is proposed to predict the concrete core confinement of the studied CFST and RuCFST columns with circular sections.